Analysis of Intact Protein Isoforms by Mass Spectrometry - Tipton, Jeremiah D. (American Society for Biochemistry and Molecular Biology, 2011)
The diverse proteome of an organism arises from such events as single nucleotide substitutions at the DNA level, different RNA processing, and dynamic enzymatic post-translational modifications. This minireview focuses on the measurement of intact proteins to describe the diversity found in proteomes. The field of biological mass spectrometry has steadily advanced, enabling improvements in the characterization of single proteins to proteins derived from cells or tissues. In this minireview, we discuss the basic technology for “top-down” intact protein analysis. Furthermore, examples of studies involved with the qualitative and quantitative analysis of full-length polypeptides are provided.